Synchronous Reference Frame Theory (SRF) Control Strategy for Optimal Operation of Double Stage Three Phase Grid Interface Multifunctional Solar Energy Conversion System - Baharudin, Nor Hanisah; Mohd Rapi, Nur Izzatie; Tunku Mansur, Tunku Muhammad Nizar; Ali, Rosnazri; Mat Suboh, Surina; Mohd Shaizad, Aini Syahida (Journal of Advanced Research Design, 2025)
Harmonic distortion, for example, is a major challenge for the electrical system. This is because this type of power quality issue can cause damage to electrical appliances, resulting in a reduced life duration for the electrical appliances; consequently, it is critical to keep the harmonic below 8%. DSTATCOM with Synchronous Reference Frame (SRF) as its control method is introduced to the system to alleviate this power quality issue, such as harmonics. SRF is in charge of generating the reference current to correct for harmonics in the system. After using DSTATCOM, all simulations for all three phases of source current achieved THD < 8%, with all phases achieving THD of 0.23%. These simulations are performed by using MATLAB/Simulink.